Respostas estratégicas de redução de incerteza face à distância institucional nas aquisições estrangeiras no Brasil - Vicente, Simone César da Silva (2014)
In this study we analyze how foreign multinational companies account for uncertainty in acquisitions in Brazil given the differences or distances, institutional separating the countries of origin of Brazil. Specifically, we look at how an extensive set of variables of the institutional environment - economic, political, financial, cultural, administrative, demographic, global connections, knowledge and geographical - that form the institutional distance impact three specific actions of foreign multinationals in acquisitions: (1) finish or not finish, its intention to carry out the acquisition of the Brazilian company, (2) the option to buy only partial ownership, as opposed to the acquisition of the entire share capital of Brazilian target, (3) to extend the time between the announcement and the effective completion of the transaction. The three action strategies examined - achievement, the degree of property acquired and the time to completion - are conceptualized as actions against the degree of uncertainty and complexity associated with operating in institutionally distant markets. Methodologically, we make an empirical study based on data collected from secondary sources, with hypothesis testing using statistical multivariate analysis. The sample consisted of 770 foreign companies from 38 countries, with intent to acquisitions of Brazilian companies in the period 2008-2012. Results showed differential impacts of dimensions of institutional distance on the actions of companies. However, supporting evidence that partial aspects of institutional distance influence the strategic behavior of multinationals on their purchases. In private, the financial distance influences the degree of implementation and the property acquired, the full institutional distance between countries was significant preference for partial or full acquisitions, and cultural and geographical distances influence the degree of acquired property. The institutional distance as a determinant for the time gap and the effective implementation is not supported in acquisitions in the period in Brazil, given the evidence that over 70% of purchases are announced and implemented simultaneously. This study contributes to the literature in two ways: it allows to understand how the institutional distance is an emerging economy through development, and assimilate the actions that companies use to variations in institutional environments in which they operate. For the practice of management, the study discusses how companies can grow to different economies institutionally minimizing uncertainties, risks and investments. The study also points to the need to analyze a set of indicators of the institutional environment and their interfaces with the company in international business, for example, in decisions to expansion core business and diversifying the use of accumulated experience in new business, thus conceptualizing not as atomistic decisions of managers of multinationals.